PENGARUH HYDRAULIC LOADING RATE (HLR) DAN KONSENTRASI INFLUEN TERHADAP PENYISIHAN PARAMETER BOD, COD DAN NITRAT PADA PENGOLAHAN AIR LIMBAH DOMESTIK CAMPURAN (GREY WATER DAN BLACK WATER) MENGGUNAKAN REAKTOR UASB - Ardina Sita Ningrum (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2012)
In this study using a mixture of domestic wastewater. Parameters to be researched is the Biological Oxygen Demand (BOD5), Chemical Oxygen Demand (COD) and nitrate-nitrogen (NO3-N). Alternative anaerobic treatment is to use UASB (upflow Anaerobic Sludge Blanket) . This study performed a variation of Hydraulic Loading Rate (HLR) and the influent concentration to obtain the optimum conditions on an UASB reactor laboratory scale for removal BOD5, COD and NO3-N in a mixture of domestic waste water (grey water and black water). Pollutant removal efficiency by varying the influent concentration and HLR for BOD5 was about 57% -76%, for COD was about 59% -69% and NO3-N was about 75% -98%. The results is the lower influent concentration will decrease removal efficiency that occurred on the parameters of BOD5, COD and NO3-N. The maximum removal efficiency on the parameters BOD5 and COD occurs when HLR low at 0.025 m3/m2/hour or 6.94 x 10-6 m / s. While the maximum removal efficiency of NO3-N occurred when HLR high 0.05 m3/m2/hour or 1.4 x10-5 m / s. Removal for BOD5 optimum occurs at low concentrations are 419 mg / l with a variation HLR of 0.05 m3/m2/hour or 1.4 x10-5 m / s, for COD occurred at low concentrations are 878 mg / l with a variation HLR of 0.025 m3/m2/hour or 6.9 x10-6 m / s, and NO3-N concentration was occur in the 36 mg / l with a variation HLR of 0.033 m3/m2/hour or 9.2 x10-6 m / s. The results of treatment using UASB still above the standards that should UASB be used as a secondary treatment to obtain the effluent below quality standart.